State-owned bullion banking through gold institutionalization as the foundation of Indonesia's economic sovereignty - Alif Asy’ari; Fauzia Gustarina Cempaka Timur; Aulia Akmalina (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: The freezing of USD 300 billion in Russian reserves by Western nations in February 2022 exposed a critical vulnerability: foreign exchange reserves have become weaponized instruments of geopolitical coercion. For developing economies, this shift has prompted reassessment of reserve composition and ownership. Gold, with jurisdictional independence and absence of counterparty risk, has re-emerged as a strategic hedge against financial coercion, sanctions, and currency dependencies. Indonesia, a resource-rich developing economy integrated into the global financial system, faces pressures to balance monetary stability with strategic autonomy. This article examines how Indonesia institutionalizes gold as economic resilience through legal, regulatory, and institutional innovation. Methods Qualitative research design using conceptual and policy-oriented analytical approaches. The study relies on document analysis and systematic literature review to examine regulatory structures, institutional governance, and their strategic implications, interpreted within political economy and security studies without conducting original quantitative estimation. Findings: The article identifies a tripartite gold ecosystem (upstream: Bullion supply chain actors; midstream: Bank Indonesia; downstream: Bullion distributors) and proposes three institutional pillars: (1) Structure & management of financial reserves; (2) Open and Fair Institutional Governance; and (3) Shifting to Security Instrument in Strategic Realm. Conclusion: Gold's strategic value is institutionally contingent. Recent reforms position Pegadaian as a state-owned bullion bank transforming sovereign reserves into operational liquidity, household inclusion, and non-kinetic resilience. This represents quiet hedging constructing parallel institutional capacity for strategic autonomy without rejecting dollar integration or accepting weaponization vulnerability. Novelty/Originality of this article: This work fills a critical gap by connecting gold reserve policy to institutional design and security governance in a Global South context. Unlike existing macro-reserve or enforcement-centric literature, it integrates political economy, institutional economics, and gray-zone theory to demonstrate how gold institutionalization simultaneously addresses macroprudential resilience, domestic value retention, and illicit finance prevention.